The urgency of legal considerations in judges decisions on the implementation of Coerced Money (Dwangsom) - Aldi Subhan Lubis; Revi Fauzi Putra Mina; Andi Hakim Lubis (Priviet Social Sciences Journal, 2025)
This study aims to determine whether the application of forced money (dwangsom) in a judge's decision is a coercive legal instrument to ensure voluntary implementation of a civil decision by the losing party. However, in practice, the absence of standard operating procedures and consistent legal considerations from judges in imposing or rejecting dwangsom create legal uncertainty. This study examines the urgency of rational, fair, and proportional legal considerations in every judge's decision related to the application of dwangsom. Normative legal research with a statutory, doctrinal, and case study approach was used. The results of the study indicate that the absence of explicit legislation regulations causes the judge to rely heavily on subjective interpretations, thereby reducing the effectiveness and coercive power of the decision. Therefore, a deep legal understanding and mature legal considerations are needed from judges when imposing dwangsom as a form of legal protection for parties with good intentions. This study also recommends judicial guidelines or regulatory updates to strengthen certainty and fairness in the application of dwangsom in civil courts.